Electron transmittance by means of quantum capacitive states as a signal amplification mechanism for biosensing applications - Garrote, Beatriz Lucas [UNESP]; Sánchez, Yuliana Pérez [UNESP]; Lopes, Laís Cristine [UNESP]; Santos, Adriano [UNESP]; Bueno, Paulo Roberto [UNESP] (Elsevier, 2024)
The use of quantum capacitive signals within redox switch interfaces is a sensitive and specific method for detecting biomolecules in a label-free format. Presently, an electrochemical signal amplification mechanism is demonstrated based on the adjustment of the energy level of quantum redox capacitive probes assembled at the interface to that of free redox probes added to the biological sample. This adjustment of the energy levels permits electron transmittance (in diffusionless mode) and communication with the electrode through the quantum redox capacitive states chemically assembled at the interface. This electron transport mode is owing to a quantum transmittance mechanism that promotes an enhancement of the electrochemical current of the interface. As quantum capacitive moieties can be chemically designed within neighboring biological receptors, an increase is observed in the electric signal sensitivity of the interface upon the binding of a biological analyte of interest by about a thousand times. The detection of the NS1 dengue virus biomarker was performed as a proof-of-concept of the above-described capacitive signal amplification methodology for biosensing, enabling the diagnosis of dengue in a point-of-care format within a limit-of-detection of 0.67 pg mL−1 in undiluted human serum samples.
Keywords: Electron transfer; Mediated charge transfer; Quantum capacitive states; Signal amplification